Entweder ästhetisch - oder religiös?: Søren Kierkegaard textanalytisch - Fürstenberg, Henrike (Kierkegaard studies, 2017)
A close analysis of the writings of Søren Kierkegaard reveals new relationships between the aesthetic and the religious. In this volume, detailed studies disclose a reciprocal conditionality that refers back to anthropological, theological, and art-theoretical premises. Thus, Kierkegaard's "aesthetic" texts propagate core religious themes, while these themes in his religious writings are established by means of aesthetic considerations